Optimization of the SiC Powder Source Material for Improved Process Conditions During PVT Growth of SiC Boules - Ellefsen, Oda Marie; Arzig, Matthias; Steiner, Johannes; Wellmann, Peter; Runde, Pål (Materials, 2019)
We have studied the influence of different SiC powder size distributions and the sublimation behavior during physical vapor transport growth of SiC in a 75 mm and 100 mm crystal processing configuration. The evolution of the source material as well as of the crystal growth interface was carried out using in situ 3D X-ray computed tomography (75 mm crystals) and in situ 2D X-ray visualization (100 mm crystals). Beside the SiC powder size distribution, the source materials differed in the maximum packaging density and thermal properties. In this latter case of the highest packaging density, the in situ X-ray studies revealed an improved growth interface stability that enabled a much longer crystal growth process. During process time, the sublimation-recrystallization behavior showed a much smoother morphology change and slower materials consumption, as well as a much more stable shape of the growth interface than in the cases of the less dense SiC source. By adapting the size distribution of the SiC source material we achieved to significantly enhance stable growth conditions.
CRIS-Team Scopus Importer:2019-10-29
Keywords: Crystal growth; In situ visualization; SiC; Source material; Sublimation